Uterine torsion in twin pregnancy with complete bicorporeal uterus, double cervix, longitudinal non-obstructing vaginal septum - a case report - Gao, Qianqian; Xiong, Jinqiu; Zhu, Yuchun (Frontiers in Surgery, 2023)
Even though uterine torsion is a rare obstetric complication in humans, it has been linked to severe complications like placental abruption, uterine rupture, foetal bradycardia, or even death. Here, we present a rare case of maternal shortening and prolonged foetal bradycardia. The patient suffered from congenital malformations of the female genital tract, which were classified as a complete bicorporeal uterus, a double “normal” cervix, and a longitudinal non-obstructing vaginal septum (U3b/C2/V1). The patient had an emergency caesarean section due to suspected placental abruption. Uterine torsion was found during the surgery, and the postoperative recovery was good. Obstetricians should be aware of the possibility of uterine torsion as a complication of pregnancy to avoid a delayed diagnosis of uterine torsion, especially in patients with genital malformations. During the surgery, there could be serious damage to blood vessels and tissues around the uterus due to an unclear surgical field, and difficulties in exposing the uterine body should be considered.